Manufacturing method of high adsorption capacity granular titanium-based lithium ion sieve adsorbent

The granular titanium-based lithium ion filter is prepared by water bath curing or vacuum drying, which solves the problem of difficult separation and cleaning of powder forms in industrial applications, and achieves a high-efficiency and low-loss lithium ion adsorption effect.

JP7653094B2Active Publication Date: 2025-03-28CHENGDU CHEMPHYS CHEM IND +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023567073
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-11-15
Filing Date
2022-11-02
Publication Date
2025-03-28
Estimated Expiration
2042-11-02

AI Technical Summary

Technical Problem

In the prior art, the powder form of lithium ion filter agent is small in size and large surface area. Although the adsorption efficiency is high, it is difficult to separate and clean in industrial applications, resulting in serious solution losses. Moreover, due to the reduction of the surface area after molding, the adsorption capacity is greatly reduced, reaching only 20-30% of the original powder.

Method used

The drip method of water bath curing or vacuum drying is used to prepare efficient granular titanium-based lithium ion filter. Through mechanical ball milling and microwave high-temperature sintering, the Li/Ti molar ratio is controlled, the porosity and strength of the material are increased, and its suspension and dispersion performance in liquid is improved.

Benefits of technology

The prepared granular titanium-based lithium ion filter has high adsorption capacity, fast adsorption and release rate, low solution loss and long life. It is suitable for various solutions with high lithium content, significantly improving the efficiency and economicality of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653094000017
    Figure 0007653094000017
  • Figure 0007653094000018
    Figure 0007653094000018
  • Figure 0007653094000019
    Figure 0007653094000019
Patent Text Reader

Abstract

The present invention relates to a method for preparing a granular titanium-based lithium ion sieve adsorbent with high adsorption capacity. The method includes the following steps: Step 1: Prepare a titanium-based lithium ion sieve precursor powder; Step 2: Prepare a granular titanium-based lithium ion sieve adsorbent with high adsorption capacity. 1) Pretreatment of the precursor powder; 2) Preparation of a composite adhesive; 3) Doping, mixing, homogenization; 4) Forming and granulation; 5) Dissolution and replacement. The granular adsorbent prepared according to the present invention has a relatively high porosity, exhibits good suspension properties when used to extract lithium from salt lake brine or simulated brine, has a high adsorption and desorption rate, and has high lithium extraction activity. The lithium ion selectivity and dissolution rate reach more than 95%. The granular adsorbent has a stable structure, low solution loss, and long cycle service life. The forming and granulation process of the granular adsorbent is simple and easy to control, and is easy to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of producing new chemical materials, and in particular to a method for producing a granular titanium-based lithium ion sieve adsorbent with high adsorption capacity. [Background technology]

[0002] Since the 21st century, with the widespread use of electronic products such as computers, digital cameras, mobile phones, and portable power tools, and the continuous development of new energy vehicles, lithium-ion batteries have become the world's largest consumer of lithium.

[0003] Natural lithium resources are mainly found in granite-type deposits, salt lake brine, seawater, and geothermal water. According to statistical data, these resources are mainly contained in lithium-containing saltwater, which accounts for about 61% of the total lithium resources. Lithium ores account for about 34% of the total, and the remaining 5% of lithium resources are found in oil fields and geothermal water.

[0004] Lithium extraction by adsorption is a new process developed in recent years to extract lithium from salt lakes. This process uses a specific lithium ion sieving absorbent to selectively adsorb lithium ions from raw salt water. This process can extract lithium from salt water with high efficiency and speed. The overall recovery rate is about 85%, which greatly improves the value and utilization rate of resources. This direction is the most competitive in lithium extraction from salt lakes. At present, researchers at home and abroad are working on the synthesis of lithium ion sieving adsorbents with stable structure, low solution loss, high adsorption capacity, and fast adsorption rate.

[0005] Due to its fine particle size, large specific surface area, and sufficient solid-liquid contact, the powdered lithium ion sieve has the advantages of large adsorption capacity and high adsorption efficiency. However, for industrial use, there are engineering problems such as difficult separation and cleaning. To solve problems such as difficult powder filtration and separation and large solution loss, the powdered lithium ion sieve needs to be molded and granulated. After granulation, the filterability and cleaning efficiency are greatly improved, and the solution loss of the adsorbent is also greatly reduced. However, because the specific surface area is reduced by molding, the adsorption capacity is greatly reduced, to only 20-30% of the original lithium ion sieve powder. In order to improve the particle size and specific surface area of ​​the adsorbent compact, researchers at home and abroad have been actively developing adsorbent molding methods in recent years, and low-cost, high-efficiency, large-scale processes and equipment have been developed. Summary of the Invention

[0006] The object of the present invention is to provide a method for producing a granular titanium-based lithium ion sieve adsorbent with high adsorption capacity, which overcomes the shortcomings of the prior art. The adsorbent is a hydrophilic granular titanium-based lithium ion sieve adsorbent. The produced granular adsorbent can efficiently and selectively identify and adsorb lithium ions in salt lake brine, lithium precipitation mother liquor, high-impurity lithium-containing solution, lithium battery recovery solution and other lithium-containing solutions. The granular adsorbent has high porosity and low specific gravity, so it can be suspended and dispersed in liquid media with small liquid impact force. The granular adsorbent can be fully and effectively contacted with salt water or eluent with fast adsorption / desorption rate and high lithium adsorption capacity. The granular adsorbent has high strength and toughness, excellent liquid impact resistance, low solution loss, and long cycle service life. The forming method adopts a slurry granulation method of solidifying in a water bath or a slurry granulation method of drying in a vacuum atmosphere. The solvent is recyclable. The forming process is simple and environmentally controllable, and the granular absorbent material can be produced on a large scale, which has high industrial value.

[0007] To achieve the above objectives, the specific technical solutions of the present invention are as follows: A method for producing a high adsorption capacity granular titanium-based lithium ion sieve adsorbent, comprising the steps of: Step 1: Step a below or The titanium-based lithium ion sieve precursor powder is prepared according to step b. Step a: Mix the lithium source, titanium dioxide, and dispersant well by mechanical ball milling, and control the molar ratio of Li / Ti to 2:(1-1.2). Add high-temperature pore-forming agent and mix well, then spray-dry to obtain granulated powder. Transfer the granulated powder to a microwave high-temperature sintering furnace and sinter at 350-650 degrees Celsius for 2-3 hours, then cool to obtain titanium-based lithium ion sieve precursor powder. Or step b) mix titanium source, lithium hydroxide and an appropriate amount of water, and control the molar ratio of Li / Ti to 2:(1-1.2). Add 0.5-1.5% by weight of hydrogen peroxide, stir and react for 3-6 hours under ultrasonic conditions at 60-90 degrees Celsius, filter, wash in sequence, add high-temperature pore-forming agent, mix well, spray dry to obtain granulated powder, transfer the granulated powder to a microwave high-temperature sintering furnace, sinter at 300-500 degrees Celsius for 2-3 hours, and cool to obtain titanium-based lithium ion sieve precursor powder. Step 2: Prepare a titanium-based lithium ion sieve adsorbent with high adsorption capacity. Step A) As a pretreatment step, the titanium-based lithium ion sieve precursor powder is pulverized and sieved through 150-800 mesh, more preferably 200-400 mesh to obtain a pretreated powder. Step B) As the preparation process of the composite adhesive, the polymer material is dissolved in an organic solvent, and an appropriate amount of additives is added, and the mixture is stirred under a water bath condition of 20 to 80 degrees Celsius until it is completely dissolved to obtain the composite adhesive. Step C) As the doping, mixing and homogenization process, the powder of step A) is mixed with the composite adhesive prepared in step B), stirred at high speed and dispersed to obtain a uniform slurry. Step D) In ​​the molding step, the mixture is molded by granulation-water bath coagulation or granulation-vacuum drying, and then sieved to obtain a granular titanium-based lithium adsorbent precursor. In step E) the elution and replacement process, lithium ions are leached from the granular titanium-based lithium adsorbent precursor of step D) using an eluent, and then washed with water to obtain a titanium-based lithium ion sieve adsorbent with high adsorption capacity.

[0008] In a preferred embodiment of the present application, the dispersant in step 1(a) is preferably one of aqueous solutions of PEG200 to PEG6000, more preferably at a concentration of 1 to 2% by weight, and the lithium source is more preferably lithium carbonate.

[0009] In a preferred embodiment of the present application, the titanium source in step 1(a) has a primary particle size of 10 to 50 nm, preferably 10 nm, and a specific surface area of ​​60 to 400 m 2 / g, preferably 300m 2 The amount of water added is 20-50% by weight of the solid mass, and the ultrasonic frequency is 20-60 KHz is more preferred.

[0010] In a preferred embodiment of the present application, the spray drying temperature in step 1 is 160-220 degrees Celsius, the high-temperature pore former is polyethersulfone, polysulfone, or polyarylsulfone, and the resulting titanium-based lithium ion sieve precursor powder is Li4Ti5O 12 Or Li2TiO3. In a preferred embodiment of the present application, the organic solvent in step B) is any one of dimethylacetamide, N-methylpyrrolidone, dimethylsulfoxide, and dichloromethane, more preferably dimethylacetamide or dimethylsulfoxide.

[0011] In a preferred embodiment of the present invention, in step B) polymer The material is any one of polyarylsulfone, polysulfone, polyethersulfone, sulfonated polysulfone, polyphenylenesulfone, polyimide, chlorinated polyvinyl chloride, and polyvinyl butyral, or a mixture thereof, and has a mass concentration of 1 to 30%, and the weight of the polymer material dissolved in the organic solvent is 5 to 20%.

[0012] The additive in step B) is any one of polyvinyl alcohol, glycerin, polysulfone, polyarylsulfone, citric acid, glucose, chitosan, oxalic acid, acetic acid, PVP, PEG6000, lithium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, or a mixture thereof, and the amount of the additive is 0-3 wt% of the mass of the high adsorption capacity titanium-based lithium ion sieve adsorbent.

[0013] In the preferred embodiment of the present application, in step C), after mixing the powder and the composite adhesive, the solid content is controlled to be 30-60% by weight, the rotation speed of the high-speed stirrer is 1100-1800 r / min, and the dispersed slurry is sieved through 80-400 mesh.

[0014] In a preferred embodiment of the present application, the coagulation bath used in the molding by water bath coagulation in step D) is either water or inorganic salt water, and the mass concentration of the inorganic salt water is 0.5 to 5% by weight. Granulation in the molding by granulation-water bath coagulation includes slurry electrostatic spray granulation, slurry brush point spray granulation, disk centrifugal granulation, etc., and the solid content concentration in the slurry is controlled to be 35 to 45%.

[0015] As a preferred embodiment of the present application, the slurry used for electrostatic spray granulation is sieved by 250-400 mesh with nozzle aperture of 0.7-1.1mm, electrostatic pressure of 3-6KV, and distance from nozzle to receptor fluid of 0.3-1m, the slurry used for brush point spray granulation is sieved by 150-300 mesh with nozzle aperture of 0.9-1.2mm, distance from nozzle to receptor fluid of 0.5-1.2m, the slurry used for disc centrifugal granulation is sieved by 80-150 mesh with disc diameter of 40-80mm, disc speed of 800-1200r / min, distance from disc to receptor fluid of 0.5-1.5m.

[0016] In a preferred embodiment of the present application, during the granulation-water bath solidification molding, the slurry is sprayed into a water tank via an electrostatic brush-stipple spray device to solidify into rod-shaped, spherical or irregular particles, or the slurry is dropped into a high-speed disk device, where the slurry is dispersed by the action of centrifugal force, sprayed into a water tank to solidify into spherical, elliptical or irregular particles, and then immersed in a coagulation bath for 0.5 to 2 hours to produce spherical, rod-shaped or irregular granular adsorbent precursor.

[0017] In a preferred embodiment of the present invention, in the molding by granulation and vacuum drying, the solid content in the slurry must first be controlled to 45-60% by weight. The droplets of the slurry are dried and molded by spraying or disc centrifugation in a vacuum atmosphere of 40-80 degrees Celsius. The vacuum degree is more preferably in the range of 0.05-0.08 MPa. Particles with a particle diameter of 0.3-2 mm are sieved as granular adsorbent precursors. In a preferred embodiment of the present application, the eluent in step E) is any one of sulfuric acid, nitric acid, hydrochloric acid, acetic acid, citric acid, oxalic acid, and Na2S2O6.

[0018] As a preferred embodiment of the present application, the technical solution of the present invention can produce a granular titanium-based lithium ion sieve adsorbent with high adsorption capacity and excellent performance. The average particle size of the granular adsorbent is preferably controlled to be 0.3-2 mm, and the bulk density is 0.35-0.45 g / cm. 3 It is.

[0019] The main solution of the present invention and its further alternatives can be freely combined to form multiple solutions, all of which can be adopted and claimed in the present invention. And each alternative can be arbitrarily combined with other compatible alternatives according to the present invention. After understanding the solution of the present invention, a person skilled in the art will have obvious combinations based on the prior art and common knowledge, all of which are technical solutions protected by the present invention and are not exhaustive here.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The prepared granular titanium-based lithium ion sieve adsorbent has good hydrophilicity, high porosity, fast adsorption / desorption rate, and high lithium adsorption capacity. It can identify and adsorb lithium in salt lake salt water, lithium precipitation mother liquor, high-purity lithium-containing solution, lithium battery recovery solution, and other lithium-containing solutions with high selectivity. The adsorbent has excellent erosion resistance, low solution loss, and long cycle life. (2) The manufacturing process of the adsorbent is simple, and the molding method adopts slurry granulation-water bath coagulation or slurry granulation-vacuum drying. The solvent can be recycled, the molding process is simple and the environment can be controlled, and the disk centrifugal granulation technology is novel, which can mass-produce granular absorbent materials and has high industrial value. (3) The produced granular adsorbent has high porosity, low specific gravity and good suspension / dispersion performance. Through the application of lithium extraction by adsorption, adsorbents of different particle size ranges can be suspended and dispersed in salt water or eluate under low impact, which increases the ion exchange rate on the adsorbent surface and reduces the energy consumption of the adsorbent during practical use. [Brief description of the drawings]

[0021] [Figure 1] 1 shows the prepared spherical titanium-based lithium ion sieve particle adsorbent. [Diagram 2] 4 shows the rod-shaped titanium-based lithium ion sieve particle adsorbent produced. [Diagram 3] 1 is a SEM micrograph of the produced titanium-based lithium ion sieve powder. [Figure 4] 1 is a SEM micrograph of a cross section of a single titanium-based lithium absorbing material. [Diagram 5] 1 shows a disc centrifugal granulator. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] A method for producing a high adsorption capacity granular titanium-based lithium ion sieve adsorbent, comprising the steps of: Step 1: Prepare titanium-based lithium ion sieve precursor powder. Step a: The lithium source, titanium dioxide, and dispersing agent are mixed well by mechanical ball mill grinding, and the molar ratio of Li / Ti is controlled to 2:(1-1.2). A high-temperature pore-forming agent is added and mixed, and spray-dried to obtain granulated powder. The granulated powder is transferred to a microwave high-temperature sintering furnace and sintered at 350-650 degrees Celsius for 2-3 hours, then cooled to obtain titanium-based lithium ion sieve precursor powder. Or step b) mix titanium source, lithium hydroxide and an appropriate amount of water, and control the molar ratio of Li / Ti to 2:(1-1.2). Add 0.5-1.5% by weight of hydrogen peroxide, stir and react for 3-6 hours under ultrasonic conditions at 60-90 degrees Celsius, filter, wash in sequence, add high-temperature pore-forming agent, mix well, spray dry to obtain granulated powder, transfer the granulated powder to a microwave high-temperature sintering furnace, sinter at 300-500 degrees Celsius for 2-3 hours, and cool to obtain titanium-based lithium ion sieve precursor powder. Step 2: Prepare a titanium-based lithium ion sieve adsorbent with high adsorption capacity. Step A) As a pretreatment step, the titanium-based lithium ion sieve precursor powder is pulverized and sieved through 150-800 mesh, more preferably 200-400 mesh to obtain a powder. Step B) As the preparation process of the composite adhesive, the polymer material is dissolved in an organic solvent, and an appropriate amount of additives is added, and the mixture is stirred under a water bath condition of 20 to 80 degrees Celsius until it is completely dissolved to obtain the composite adhesive. Step C) is a doping, mixing and homogenization process, in which the powder of step A) is mixed and dispersed with the composite adhesive prepared in step B) to obtain a uniform slurry. Step D) In ​​the molding step, the mixture is molded by granulation-water bath coagulation or granulation-vacuum drying, and then sieved to obtain a granular titanium-based lithium adsorbent precursor. Step E) As an elution / substitution process, lithium ions are leached from the titanium-based lithium adsorbent precursor of step D) using an eluent, and then washed with water to obtain a titanium-based lithium ion sieve adsorbent with high adsorption capacity.

[0023] Preferably, the dispersing agent in step 1(a) is one of glucose, citric acid, and an aqueous solution of PEG200 to PEG6000 at a concentration of 1 to 2% by weight, and the lithium source is more preferably lithium carbonate.

[0024] Preferably, the titanium source in step 1(b) has a primary particle size of 10-50 nm, more preferably 10 nm, and a specific surface area of ​​60-400 m 2 / g, preferably 300m 2 / g of titanium dioxide. The amount of water added is 20-50% of the solid mass, and the ultrasonic frequency is 20-60 KHz is more preferred.

[0025] Preferably, the spray drying temperature in step 1 is 160-200 degrees Celsius, the pore former is one of polyethersulfone, polysulfone, and polyarylsulfone, the microwave sintering temperature in step 1(a) is more preferably 450-550 degrees Celsius, and the microwave sintering temperature in step 1(b) is more preferably 350-450 degrees Celsius, and the metatitanic acid powder obtained above is Li4Ti5O 12 Or Li2TiO3.

[0026] Preferably, the organic solvent in step B) is any one of dimethylacetamide, N-methylpyrrolidone, dimethylsulfoxide, ethyl acetate and dichloromethane.

[0027] Preferably, in step B) polymer The material is any one of polyarylsulfone, polysulfone, polyethersulfone, sulfonated polysulfone, polyphenylenesulfone, polyimide, chlorinated polyvinyl chloride, and polyvinylidene fluoride, or a mixture thereof, and has a mass concentration of 1 to 30%, and the weight of the polymer material dissolved in the organic solvent is 5 to 20%.

[0028] Preferably, the additive in step B) is any one of polyvinyl alcohol, polysulfone, polyarylsulfone, citric acid, glucose, chitosan, oxalic acid, acetic acid, PVP, PEG200-PEG6000, lithium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, or a mixture thereof, and the amount of the additive is 0-3 wt % of the mass of the high adsorption capacity titanium-based lithium ion sieve adsorbent.

[0029] Preferably, in step C), after mixing the powder and the composite adhesive, the solid content is more preferably controlled to be 35-45% by weight, the rotation speed of the high-speed stirring is 1100-1800 r / min, and the dispersed slurry is sieved through 80-400 mesh.

[0030] Preferably, the coagulation bath used in the molding by granulation-water bath coagulation in step D) is either water or inorganic salt water, and the mass concentration of the inorganic salt water is 0.5 to 5%.

[0031] Preferably, the granulated material granulated by granulation-water bath coagulation includes slurry electrostatic spray granulation, slurry brush point spray granulation, and disk centrifugal granulation, the solid content in the slurry is controlled to 35-45%, the slurry is sprayed into a water tank through an electrostatic brush-stipple spray device to coagulate into rod-shaped, spherical or irregular particles, or the slurry is dropped into a high-speed disk device, the slurry is dispersed by the action of centrifugal force, sprayed into a water tank to coagulate into spherical, elliptical or irregular particles, and immersed in a coagulation bath for 0.5-2 hours to produce spherical, rod-shaped or irregular granular adsorbent precursor.

[0032] Preferably, the slurry used in electrostatic spray granulation is sieved by 250-400 mesh with nozzle aperture of 0.7-1.1mm, electrostatic pressure of 3-6KV, and distance from nozzle to receptor fluid of 0.3-1m, the slurry used in brush point spray granulation is sieved by 150-300 mesh with nozzle aperture of 0.9-1.2mm, distance from nozzle to receptor fluid of 0.5-1.2m, the slurry used in disc centrifugal granulation is sieved by 80-150 mesh with disc diameter of 40-80mm, disc speed of 800-1200r / min, distance from disc to receptor fluid of 0.5-1.5m.

[0033] Preferably, in the molding by granulation-vacuum drying and solidification, the solid content in the slurry must first be controlled to 45-60%, the vacuum range is 0.03-0.09 MPa, the drying temperature is 40-80 degrees Celsius, and the sieved particle size is 0.3-2 mm.

[0034] Preferably, the eluent used to leach the particulate lithium ion precursor in step E) is any one or a combination of sulfuric acid, hydrochloric acid or Na2S2O6.

[0035] By the above method, a granular titanium-based lithium ion sieving adsorbent having a high adsorption capacity is produced. By the above-mentioned method of the present invention, a granular titanium-based lithium ion sieving adsorbent having a high adsorption capacity and excellent performance is produced. The particle size of the granular adsorbent is preferably controlled to 0.3 to 2 mm, and the bulk density is preferably 0.35 to 0.45 g / cm. 3 It is.

[0036] Hereinafter, the implementation of the present invention will be described through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific implementation forms, and various details in the description can be modified or changed based on different perspectives and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features of the embodiments can be combined with each other in a non-conflicting situation.

[0037] In order to clearly understand the objectives, technical solutions and advantages of the present invention, it should be noted that the technical solutions of the embodiments of the present invention are clearly and completely described below in combination with the figures of these embodiments. Obviously, the embodiments described herein are only a part, rather than all, of the embodiments of the present invention. In general, the components of the embodiments of the present invention described herein and illustrated in the figures can be arranged and designed in various configurations.

[0038] In the data analysis in the following examples, K, Ca, Na, Mg, and B are measured by ICP spectroscopy, Cl by spectrophotometric colorimetry, Li and Ti by atomic absorption spectrometry, and sulfate by barium sulfate turbidimetry. (GB13580.6-92) In the present specification, % refers to mass percentage, i.e., % by weight, unless otherwise specified.

[0039] EMBODIMENT 1 A method for producing a high adsorption capacity granular titanium-based lithium ion sieve adsorbent, comprising the steps of: (1) Preparation of lithium metatitanate powder 19.7 kg of titanium dioxide, 17.4 kg of lithium carbonate for batteries, and 0.1 kg of 1.5 wt % PEG6000 aqueous solution are dispersed and mixed uniformly at high speed, mechanically crushed by ball mill to control the particle size D50 = 550 ~ 850 nm, then polyethersulfone powder is mixed and spray pre-granulated, the spray pre-granulation temperature is set to 200 degrees Celsius, and finally, it is baked at 600 degrees Celsius in a microwave oven to obtain lithium ion sieve precursor Li2TiO3. (2) PES-H2TiO3 rod-shaped adsorbent S1: Pretreatment: The lithium metatitanate precursor is crushed and sieved through a 250 mesh to obtain lithium metatitanate lithium ion precursor. S2: Preparation of 15% PES sol: Add 2.7 kg of granular PES (polyethersulfone) to 15 L of dimethylacetamide and stir continuously for 2 h in a 50 degree Celsius water bath until completely dissolved to obtain 15% PES (% is the percentage of polymeric material in the solvent). S3: Doping, mixing and homogenization: Take 9 kg of Li2TiO3 powder pretreated in step S1 and all the 15% PES sol obtained in step S2, mix them uniformly at a speed of 1800 r / min by mechanical stirring, and obtain a mixed slurry by ultrasonication for 15 min. S4: Molding: The mixed slurry is sieved through a 250 mesh, extrusion granulated by an electrostatic solution spray device, and solidified in a water tank. The voltage is adjusted to 6 kv and the receiving distance to 0.5 m to obtain a spherical lithium-ion sieve precursor material, and the particles of 0.3 to 2 mm are sieved with a yield of more than 95% (measured particle size distribution is 0.3 to 0.5 mm 20%, 0.5 to 0.7 mm 20%, 0.7 to 0.9 mm 30%, 0.9 to 1.1 mm 20%, 1.1 to 1.5 mm 5%, 1.5 to 2 mm 5%) as a molding precursor. The average bulk density is 0.43 g / cm. 3 The absorbent having this ratio can be suspended and dispersed in the simulated salt water 1 at a bubbling flow rate of 0.15 Bv / min, and can be suspended and dispersed in the eluate at a bubbling flow rate of 0.35 Bv / min. S5: Replacement: Lithium ions are extracted from the granular precursor obtained in step S4 with 0.4M HCl, and the granular precursor is washed to obtain a PES-HTO adsorbent. The PES-HTO adsorbent prepared in this embodiment is used to perform dynamic adsorption tests on the adsorption columns of simulated salt water 1 and simulated salt water 2. The specific evaluation results are as follows:

[0040] [Table 1]

[0041] [Table 2]

[0042] Lithium metatitanate (Li2TiO3) powder is dynamically dissolved in 0.4 mol / L hydrochloric acid for 20 hours to obtain lithium ion sieve HTO powder. The evaluation results of Li adsorption and desorption performance are as follows.

[0043] [Table 3]

[0044] [Table 4]

[0045] EMBODIMENT 2 (1) Preparation of lithium metatitanate powder Take 40 kg of titanium dioxide and 10 kg of water, mix and grind into a uniform slurry, add 10.5 kg of solid lithium hydroxide, mix and stir uniformly, and mix 40 KHz Heated to 60 degrees Celsius at ultrasonic frequency of , stirred reaction under normal pressure for 6 hours, added hydrogen peroxide drop by drop during the reaction process (total of about 100mL of 30% hydrogen peroxide), filtered and scrubbed titanium-based lithium ion sieve powder after reaction, returned the filtrate to the slurry mixing for recycling, beaten the slurry, added 0.1kg of polymer pore former polyethersulfone, mixed uniformly, spray pre-granulated, calcined at 450 degrees Celsius in air atmosphere for 3 hours, cooled to room temperature to obtain metatitanate lithium ion sieve Li2TiO3. (2) PES-H2TiO3 rod-shaped adsorbent The manufacturing process of the PES-H2TiO3 rod-shaped adsorbent is the same as that of the first embodiment, but differs in that a disk centrifuge is used for granulation. The slurry is sieved with 80 mesh, the diameter of the disk is 60 mm, the rotation speed of the disk is controlled to 950 r / min, the distance from the receptor liquid is 0.5 m, and the receptor coagulation bath is a 1.5 wt% sodium bisulfate aqueous solution, so that a 0.3-2 mm spherical adsorbent (PES-H2TiO3) is prepared and sieved, with a yield of 95% or more (measured particle size distribution is 0.3-0.5 mm 20%, 0.5-0.7 mm 20%, 0.7-0.9 30%, 0.9-1.1 mm 20%, 1.1-1.5 mm 5%, 1.5-2 mm 5%). The average bulk density is 0.44 g / cm 3 This ratio of absorbent can be suspended and dispersed in the simulated salt water 1 at a bubbling flow rate of 0.2 Bv / min, and can be suspended and dispersed in the eluate at a bubbling flow rate of 0.4 Bv / min.

[0046] The granular adsorbent produced in this embodiment was subjected to a columnar dynamic adsorption test, and lithium extraction was evaluated by simulations 1 and 2, respectively.

[0047] The lithium metatitanate (Li2TiO3) powder prepared in this embodiment was dynamically dissolved in 0.4 mol / L hydrochloric acid for 20 hours to obtain lithium ion sieve HTO powder, and the lithium extraction was evaluated by simulations 1 and 2, respectively.

[0048] [Table 5]

[0049] [Table 6]

[0050] EMBODIMENT 3 The manufacturing method of the adsorbent is basically the same as that of embodiment 2, except for step S2. Add 2.7 kg of granular PES (polyethersulfone) to 15 L of dimethylacetamide, add additive PEG6000 (accounting for 2.5% of the molded adsorbent), and continuously stir in a water bath at 50 degrees Celsius for 2 hours until completely dissolved, to obtain a 15% PES sol (% is the proportion of polymer material in the solvent).

[0051] PES-PEG-H2TiO3 rod-shaped adsorbent The granular lithium ion sieve PES-PEG-HTO prepared in this embodiment was used in a columnar dynamic adsorption test. The salt water used in this embodiment is the same as that in embodiment 1, and the test results are as follows:

[0052] [Table 7]

[0053] Comparative Example 1 The method for producing the adsorbent is basically the same as in the third embodiment, except that a polymer material, PVDF (polyvinylidene fluoride), is used as the molding substrate instead of PES to produce a PVDF-H2TiO3 composite adsorbent.

[0054] Comparative Example 2: The manufacturing method of the adsorbent is basically the same as that of the third embodiment, but the difference is that the PVDF-H2TiO3 composite adsorbent is prepared by using the polymer material PVDF (polyvinylidene fluoride) instead of PES as the molding substrate. The adsorbents obtained in the first and second comparative examples were subjected to a columnar dynamic adsorption test under the same test conditions as those in the first embodiment. The test results are as follows:

[0055] [Table 8]

[0056] From the above table, it can be seen that the elution performance of the PVDF-H2TiO3 and PTFE-H2TiO3 composite adsorbents obtained in Comparative Example 1 and Comparative Example 2 is poor.

[0057] EMBODIMENT 4 The manufacturing method of the adsorbent is basically the same as that of embodiment 2, except for step S2. 2.7 kg of granular PES (polyethersulfone) is added to 15 L of dichloromethane, and additive PEG6000 (accounting for 2.5% of the molded adsorbent) is added, and the mixture is continuously stirred at room temperature for 2 hours until completely dissolved, to obtain a 15% PES sol (% is the proportion of polymer material in the solvent). The mixed slurry is sieved through a 300 mesh and granulated using a vacuum spray device controlled at a vacuum degree of 0.06 MPa and 25 degrees Celsius. Dichloromethane is recovered through a vacuum condensation system. After sieving, the average bulk density is 0.43 g / cm 3 It is possible to obtain rod-shaped adsorbent (PES-H2TiO3) of 0.3 to 2 mm. The specific test results of the absorbent are as follows:

[0058] The granular lithium ion sieve PES-PEG-HTO prepared in this embodiment was used in a columnar dynamic adsorption test. The salt water used in this embodiment is the same as that in embodiment 1, and the test results are as follows:

[0059] [Table 9]

[0060] Experiment 1: The performance of the adsorbents prepared under different conditions was tested. The manufacturing method is the same as that of embodiment 3, and the only difference is that the solvent, polymer material, additive, molding method, and shape of the obtained adsorbent are replaced according to the table below. Embodiments 5 to 29 are obtained, respectively. The specific differences are as follows.

[0061] [Table 10]

[0062] A columnar dynamic adsorption test was carried out on the adsorbents obtained in the embodiments 5 to 29. The saltwater in the adsorption test has the same index as the simulated saltwater 2 in the embodiment 1. The experimental results are as follows.

[0063] [Table 11]

[0064] Experiment 2: Life test The C-PVC-PASF-HTO granular composite adsorbent prepared according to the conditions of embodiment 23 was subjected to a life test experiment, and the simulated saltwater was subjected to 1000 industrial continuous unidirectional dynamic adsorption and desorption cycles. The saltwater used in this embodiment is the same as the simulated saltwater 1 in embodiment 1. The specific test results are as follows:

[0065] [Table 12]

[0066] From the above table, it can be seen that after 1000 cycles the lithium adsorption capacity of the adsorbent decreases but is still above 6 mg / g.

[0067] Comparative Example 3 The lithium ion sieve precursor powder prepared in Example 2 was pulverized and sieved through a 250 mesh, and 70 g of Li2TiO3, 20 g of modified acrylic water-based resin (50%), and 10 g of water were weighed and thoroughly mixed to control the effective ratio of the powder in the molding material to 89%, and extruded into small columnar particles with a diameter of 1.5 mm using a granulator, dried at 80 degrees Celsius for 24 hours to obtain an adsorbent precursor, and then immersed in 1MHCL for 24 hours to obtain a particle adsorbent.

[0068] Comparative Example 4 The lithium ion sieve precursor powder prepared in embodiment 2 is ground and sieved through 250 mesh, Li2TiO370g, Fe2O310g, diatomaceous earth20g are weighed and mixed, 20g epoxy resin adhesive is added to the mixed powder of the previous step, and small columnar particles with a diameter of 1.5mm are formed through an extrusion granulator, and sent to an oven to dry at 80 degrees Celsius for 2 hours, and the dried particles are immersed in 1MHCl for 4 hours, maintained at 60 degrees Celsius, and scrubbed to obtain cylindrical lithium ion sieve particles.

[0069] The performance of the adsorbents prepared in Comparative Example 3 and Comparative Example 4 was compared with that of the adsorbent prepared in Example 24. A test was performed using the simulated salt water 1 of Example 1 (adsorption for 1.5 hours, elution with 0.1M sulfuric acid for 1.5 hours) to measure the porosity of the granular adsorbent. The mass loss of the adsorbent under the same conditions was measured by ultrasonic vibration to evaluate the strength of the adsorbent. The results are shown in the following table.

[0070] [Table 13]

[0071] Porosity measurement: Place approximately 100 mL of adsorbent in a 200 mL measuring cylinder, add water until the adsorbent is saturated with water adsorption, and after ultrasonic treatment, absorb the water that overflows from the surface with filter paper and record the amount of water adsorption V0. Continue adding water up to the 250 mL mark, record the amount of water replenishment V1, and the porosity Φ = V0 / (250-V1) x 100%.

[0072] Strength evaluation of the sorbent precursor: 5 g of the formed membrane-shaped lithium ion sieve precursor that had been dried to a constant weight was weighed out, placed in a test tube containing distilled water and sealed. The test tube was then cooled to 40 KHz After placing it in an ultrasonic oscillator and oscillating it for 30 minutes, it was taken out, suction filtered, and dried until it reached a constant weight. The mass mi of the lithium ion sieve precursor was then weighed (i=1, 2, 3, weighed on an analytical balance), and this was repeated three times to obtain the average value, from which the average mass loss rate Φm was calculated.

[0073]

number

[0074] Experiment 3: lithium precipitation mother liquor adsorption experiment: 50g of the granular lithium ion sieve prepared in embodiment 25 was weighed and immersed in 2L of 1700mg / L lithium precipitation mother liquor, and the first water sample was taken after 2 hours to test the lithium content, and then samples were taken every hour to test the lithium content until there was no difference in the lithium content between two adjacent samples, and when the adsorption reached saturation, the saturated adsorption capacity of the lithium ion sieve was calculated. The specific test results are shown in the table below.

[0075] [Table 14]

[0076] Experiment 4 - Example of the production of an adsorbent with good suspension performance The manufacturing process is the same as that of embodiment 23, but the manufactured adsorbent contains 60% effective powder, 2.5% added polymer mixture, and 37.5% composite polymer. The particle size range of the prepared granular adsorbent is 0.3-2 mm, and the particle size distribution is 15% 0.3-0.5 mm, 15% 0.5-0.7 mm, 30% 0.7-0.9, 20% 0.9-1.1 mm, 10% 1.1-1.5 mm, and 10% 1.5-2 mm. The average bulk density is 0.35 g / cm. 3 The granular adsorbent can be suspended and dispersed in simulated salt water from bottom to top at a density of 1.2, and can also be suspended and dispersed in the eluate with a gas flow rate of 0.1 Bv / min. The evaluation results of bubbling dynamic adsorption at 0.1 Bv / min are as follows.

[0077] [Table 15]

[0078] From the above table, it can be seen that the granular ion sieve adsorbent prepared by the present invention has good adsorption performance, and by adjusting the proportion of polymer in the formulation and the particle size distribution, it is possible to obtain absorbent materials with different suspension characteristics, and it is possible to use different salt water and lithium-containing solutions, so it has high industrial value. Note: % titanium loss, dissolution and recovery are calculated (by mass) according to industry standard formulas.

[0079] The above-mentioned basic embodiment of the present invention and its further options can be freely combined to form multiple embodiments, which the present invention can adopt and claim. In the solution of the present invention, each option can be arbitrarily combined with other basic embodiments or options. It is obvious to those skilled in the art that many combinations exist.

[0080] All the above are only preferred embodiments of the present invention, and do not limit the scope of the present invention. Without departing from the spirit and principle of the present invention, all modifications, equivalent replacements and improvements shall be included in the protection scope of the present invention.

Claims

1. A method for producing a high adsorption capacity granular titanium-based lithium ion sieve adsorbent, comprising the steps of: Step 1: Prepare a titanium-based lithium ion sieve precursor powder by the following step a or step b: Step a: mixing lithium source, titanium dioxide and dispersant thoroughly by mechanical ball milling, controlling the molar ratio of Li / Ti to 2:(1-1.2), adding high-temperature pore-forming agent and mixing thoroughly, spray drying to obtain granulated powder, transferring the granulated powder to a microwave high-temperature sintering furnace and calcining at 350-650 degrees Celsius for 2-3 hours, and cooling to obtain titanium-based lithium ion sieve precursor powder; or step b) mixing titanium source, lithium hydroxide and an appropriate amount of water, controlling the molar ratio of Li / Ti to 2:(1-1.2), adding 0.5-1.5 wt% hydrogen peroxide, stirring and reacting under ultrasonic conditions at 60-90 degrees Celsius for 3-6 hours, filtering and washing in sequence, adding high-temperature pore-forming agent and mixing well, spray-drying to obtain granulated powder, transferring the granulated powder to a microwave high-temperature sintering furnace, firing at 300-500 degrees Celsius for 2-3 hours, and cooling to obtain titanium-based lithium ion sieve precursor powder; Step 2: Prepare a titanium-based lithium ion sieve adsorbent with high adsorption capacity; Step A) As a pretreatment step, the titanium-based lithium ion sieve precursor powder is pulverized and sieved through a 150-800 mesh to obtain a pretreated powder; Step B) preparing the composite adhesive, dissolving the polymer material in an organic solvent, adding an appropriate amount of additives, and stirring under a water bath condition of 20-80 degrees Celsius until completely dissolved to obtain the composite adhesive; Step C) as a doping and mixing process, mix the powder of step A) with the composite adhesive prepared in step B) and stir at high speed to uniformly disperse the powder and obtain a uniform slurry; Step D) as a forming step, the slurry of step C) is formed by granulation-water bath coagulation or granulation-vacuum drying, and particles of 0.3 to 2 mm are collected and sieved to obtain a granular titanium-based lithium adsorbent precursor; Step E) as an elution / substitution step, leaching lithium ions from the granular titanium-based lithium adsorbent precursor of step D) using an eluent, and then washing with water to obtain a titanium-based lithium ion sieve adsorbent with high adsorption capacity; A method for producing a high adsorption capacity granular titanium-based lithium ion sieve adsorbent, characterized by:

2. 2. The method according to claim 1, wherein the dispersing agent in step a is any one of glucose, citric acid, and PEG200 to PEG6000 aqueous solutions having a solution concentration of 1 to 2% by weight, and the lithium source is lithium hydroxide or lithium carbonate.

3. The titanium source in step b is metatitanic acid or titanium dioxide having a primary particle size of 10 to 50 nm and a specific surface area of ​​60 to 400 m 2 / g, the amount of water added is 20 to 50% by weight of the solid mass, and the ultrasonic frequency range is 20 to 80 KHz.

4. The spray drying temperature in step 1 is 160-220 degrees Celsius, the high temperature pore former is one of polyethersulfone, polysulfone, and polyarylsulfone, and the resulting titanium-based lithium ion sieve precursor powder is Li 4 Ti 5 O 12 Or Li 2 TiO 3 The method according to claim 1 ,

5. 2. The method according to claim 1, wherein the organic solvent in step B is any one of dimethylacetamide, N-methylpyrrolidone, dimethylsulfoxide, and dichloromethane.

6. 2. The method according to claim 1, wherein the polymer material in step B is any one of polyarylsulfone, polysulfone, polyethersulfone, sulfonated polysulfone, polyphenylenesulfone, polyimide, chlorinated polyvinyl chloride, and polyvinyl butyral, or a mixture thereof, and the mass concentration of the polymer material dissolved in the organic solvent is 5 to 20% by weight.

7. The method according to claim 1, characterized in that the additive in step B is polyvinyl alcohol, glycerin, polysulfone, polyarylsulfone, citric acid, glucose, chitosan, oxalic acid, acetic acid, PVP, PEG6000, lithium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate or any mixture thereof, and the amount of the additive is 0-3 wt% of the mass of the high adsorption capacity titanium-based lithium ion sieve adsorbent.

8. The manufacturing method as claimed in claim 1, characterized in that in step C, after mixing the powder and the composite adhesive, the solid content is controlled to be 30-60 wt%, the rotation speed of the high-speed stirring is 1000-2500 r / min, and the dispersed slurry is sieved through 80-400 mesh.

9. The method according to claim 1, wherein a coagulation bath used in the molding by granulation and water bath coagulation in step D is either water or inorganic salt water, and a mass concentration of the inorganic salt water is 0.5 to 5% by weight.

10. The eluent in step E is sulfuric acid, nitric acid, hydrochloric acid, acetic acid, citric acid, oxalic acid, Na 2 S 2 O 6 The method according to claim 1, characterized in that the method is any one of the above.

11. The method according to claim 1 or 7, characterized in that the granulation during the molding by granulation-water bath solidification includes slurry electrostatic spray granulation, slurry brush point spray granulation, and disk centrifugal granulation, the solid content in the slurry is controlled to 35-45% by weight, the slurry used for electrostatic spray granulation is sieved by 250-400 mesh with a nozzle opening of 0.7-1.1 mm, an electrostatic pressure of 3-6 KV, and a distance from the nozzle to the receptor fluid of 0.3-1 m, the slurry used for brush point spray granulation is sieved by 150-300 mesh with a nozzle opening of 0.9-1.2 mm, a distance from the nozzle to the receptor fluid of 0.5-1.2 m, and the slurry used for disk centrifugal granulation is sieved by 80-150 mesh with a disk diameter of 40-80 mm, a disk speed of 800-1200 r / min, and a distance from the disk to the receptor fluid of 0.5-1.5 m.

12. The manufacturing method according to claim 1, characterized in that in the molding by granulation-vacuum drying, it is necessary to first control the solid content concentration in the slurry to 45-60% by weight, the vacuum degree range is 0.03-0.09 MPa, the drying temperature is 40-80 degrees Celsius, and the sieved particle size is 0.5-2 mm.

13. A high-capacity granular titanium-based lithium ion sieve adsorbent, which is produced by the method according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Preparation method of granular lithium adsorbent

    CN109225124A

  • Titanate-based lithium absorber and manufacturing method therefor

    JP2017177064A

  • Method for producing titanium-based lithium ion exchanger

    JP2024522951A